The role of Eph receptors and Ephrins in the skin. (24th October 2015) - Wijeratne, Dulharie T.; Rodger, Jennifer; Wood, Fiona M.; Fear, Mark W.
Abstract: Eph receptors and Ephrin ligands are widely expressed in the skin. Various studies have been carried out to identify the effects of these molecules on many aspects of skin development. Here we summarize the literature that has identified roles for Eph receptors and Ephrins in the skin, focusing mainly on the epidermis, hair follicles, and cutaneous innervation. This review may help direct and focus further investigations into the role of Eph receptors and Ephrins in the development, maintenance, and repair processes in cutaneous biology.